Tellurium Photonic Crystal-Based Terahertz Polarization Splitter Using a Diamond-Shaped Ferrite Pillar Array - Haiping Zhang; Zhifeng Zeng; Yong Wang (Crystals)
A T-shaped photonic crystal waveguide was designed with square lattice tellurium photonic crystals. A diamond-shaped ferrite pillar array was inserted in the junction of the waveguide to make a novel terahertz polarization splitter. Both transverse electric and transverse magnetic modes were numerically investigated by the plane wave expansion method, which used complete photonic band gaps covering from 0.138 THz to 0.144 THz. In this frequency domain of the fully polarized band gaps, the transmission efficiency of the photonic crystal waveguide was up to −0.21 dB and −1.67 dB for the transverse electric and transverse magnetic modes, respectively. Under the action of a DC magnetic field, the THz waves were rotated 90 degrees by the diamond-shaped ferrite pillar array. Transverse electric waves or transverse magnetic waves can be separated by a polarization isolator (six smaller tellurium rods) from the fixed waves. The characteristics of the designed polarization splitter were analyzed by the finite element method, and its transmission efficiency was optimized to 95 percent by fine-tuning the radii of the thirteen ferrite pillars. A future integrated communication network of sky–earth–space will require fully polarized devices in the millimeter and terahertz wavebands. The envisaged polarization splitter has a unique function and provides a promising method for the realization of fully polarized 6G devices.